Pengaruh Distribusi Pendapatan, Investasi Dan Politik Terhadap Perekonomian Di Indonesia - Adib Rafi Darmadi; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This type of research is descriptive and associative research, the data used in this study is secondary data using panel data techniques during the 2015-2019 period. Documentation data collection techniques obtained from the Central Statistics Agency (BPS). Data were analyzed using panel regression with Random Effect Model (REM) selection test.The results of this study indicate that simultaneously, gender inequality, dependency ratio and health have a significant influence on poverty in Indonesia. Furthermore, partially (1) Gender inequality has a negative and insignificant effect on poverty in Indonesia (2) The dependency ratio has a positive and insignificant effect on poverty in Indonesia and (3) Health has a negative and significant effect on poverty in Indonesia.